Effects of non-thermal plasma jet treatment of Pure/Doped Polystyrene thin films on UV-Vis optical properties - Goodson, Mersaydes; Xu, Kunning G.; Guggilla, Padmaja (European Journal of Applied Sciences, 2022)
Non-thermal Cold Atmospheric Plasma (CAP) to improve optical property of pure and doped polystyrene (PS) thin films using He and Ar gas. These thin films were fabricated using the solution cast method. Surface treatment of PS thin films were performed by CAP. To analyze the effect of plasma treatment, the optical properties of the thin films were measured and derived by UV-Vis spectroscopy in wavelength range of 300-700 nm. Absorbance, transmittance, extinction coefficient, energy band gap, and optical conductivity before and after Cold jet plasma treatment (CJT) were compared. The results from Ar and He were similar in effectiveness. The treatment did have an impact on the optical properties of these PS thin films. This data will help to substantiate the use of CJT to enhance optical properties of polymer thin films.